2011
DOI: 10.1074/jbc.m110.167098
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-based, Homology Model of the Extracellular Domain of the Epithelial Na+ Channel α Subunit Reveals a Mechanism of Channel Activation by Proteases

Abstract: The epithelial Na ؉ channel (ENaC) mediates Na ؉ transport across high resistance epithelia. This channel is assembled from three homologous subunits with the majority of the protein's mass found in the extracellular domains. Acid-sensing ion channel 1 (ASIC1) is homologous to ENaC, but a key functional domain is highly divergent. Here we present molecular models of the extracellular region of ␣ ENaC based on a large data set of mutations that attenuate inhibitory peptide binding in combination with comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 52 publications
4
84
0
Order By: Relevance
“…1A). We recently showed that N-Cys can be cross-linked to E174C but not E173C (11). We mutated each of the remaining sites to Cys and attempted to cross-link these mutants to both N-Cys and C-Cys using bifunctional MTS compounds with alkanediyl linkers of various lengths.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1A). We recently showed that N-Cys can be cross-linked to E174C but not E173C (11). We mutated each of the remaining sites to Cys and attempted to cross-link these mutants to both N-Cys and C-Cys using bifunctional MTS compounds with alkanediyl linkers of various lengths.…”
Section: Resultsmentioning
confidence: 99%
“…Except for Y474C, successful cross-linking depended on the length of the alkanediyl linker of the MTS compound. Of the sites 170 -175 at the N terminus of helix ␣1, we previously examined MTS-4-MTS cross-linking of N-Cys and C-Cys to Cys introduced at Glu-173 and Glu-174 (11). These data provided evidence for cross-linking between E174C and N-Cys but not cross-linking involving E173C.…”
Section: Peptidementioning
confidence: 99%
See 2 more Smart Citations
“…Sequencing the two tm1552 transcripts revealed that the large transcript introduced a pre- mature stop codon after Ile 189 . The small but more abundant transcript encoded a MEC-10 protein with an in-frame deletion of 150 residues (Ala 162 -Lys 311 ) from a peripheral part of the extracellular region that is poorly conserved among members of the ENaC/degenerin family, referred to as the finger domain (33,34). We generated both gene products, MEC-10 L190X and MEC-10 ⌬162-311, and examined the LSS response of channels containing these MEC-10 mutants.…”
Section: Mec-4dmentioning
confidence: 99%